EXPLORING THE POTENTIAL OF THE SHARIA ECONOMY IN THE MIDST OF THE DIGITAL REVOLUTION - tuhah, Maftuhah maf; Muhlis, Muhlis; Permanasari, Lukita; Fitriyah, Duta Bintan (ADILLA : Jurnal Ilmiah Ekonomi Syari'ah, 2025)
The digital revolution has brought significant changes to various economic sectors, including Islamic economics. This study aims to explore the potential of Islamic economics in the digital era by analyzing the opportunities and challenges faced. The research employs a qualitative approach, conducting a literature review on the digitalization of Islamic economics from both micro and macroeconomic perspectives. The findings indicate that digitalization in Islamic economics can enhance efficiency, accessibility, and transparency of transactions. Technological innovations such as Islamic fintech and halal e-commerce platforms play a crucial role in expanding the reach of Islamic financial services. However, challenges such as low digital literacy, inadequate technological infrastructure, and the lack of supportive regulations remain obstacles in the development of Islamic economics in the digital era. Therefore, government support in the form of appropriate regulations and the enhancement of public digital literacy are essential to maximize the potential of Islamic economics in the digital era. Collaboration among the government, industry players, and the community is key to addressing challenges and leveraging existing opportunities.